Pengaruh Perlakuan Seed Coating dan Periode Simpan terhadap Benih Jagung (Zea mays. L) - Yohanes Theodorus Natasi (Fakultas Pertanian, Universitas Timor, 2021)
Corn (Zea mays L) is one of the most productive food plants in the world, including in Indonesia. The existence of corn is familiar to the world community because corn is one of the cereals which has an important role besides rice and wheat. The purpose of this study was to determine the benefits of PGPR in the treatment of seed coating during the storage period. Using a Completely Randomized Design (CRD) Factorial Pattern. Factor 1 is the coating composition, namely C0 = No coating, C1 = coating with PGPR, C2 = Coating with MOL (Local Microorganisms). Factor 2 is a storage period consisting of 2 levels, namely P0 = No storage, P1 = Storage 1 month, P2 = Storage 2 Months, P3 = Storage 3 Months. Anova variance results show that there is an interaction between the coating treatment of maximum growth potential, germination, vigor index, growth speed, growth synchronization, normal germination dry weight and disease incidence.